2022
DOI: 10.1007/s00520-022-06975-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of photobiomodulation therapy for the prevention of chemotherapy-induced peripheral neuropathy: a randomized, placebo-controlled pilot trial (NEUROLASER trial)

Abstract: Purpose The purpose of this study was to investigate the effectiveness of photobiomodulation (PBM) therapy for the prevention of chemotherapy-induced peripheral neuropathy (CIPN) in breast cancer patients. Methods A prospective, randomized placebo-controlled pilot trial (NEUROLASER) was set up with 32 breast cancer patients who underwent chemotherapy (ClinicalTrials.gov; NCT03391271). Patients were randomized to receive PBM (n = 16) or placebo treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Seventeen studies reported pain-alleviating, involving 956 participants [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Among these studies, three studies applied ES as an intervention, including scrambler therapy [14], low-frequency electrical stimulation [16], and neurofeedback therapy [17], 16 studies focused on UCP, two studies adopted interventions pooled as Yoga [15,18], two studies used massage [19,27], two studies used interventions pooled as Edu, including cognitive behavioral therapy [20] and electronic symptom management system [22], six studies used Acu [23-26, 29, 30], one used vitamin and gabapentin (VG [24]), one used photobiomodulation (PBM [21]), and one used ME [28]. There were statistical differences between massage and Acu, VG, and UCP.…”
Section: Primary Outcomes Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies reported pain-alleviating, involving 956 participants [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Among these studies, three studies applied ES as an intervention, including scrambler therapy [14], low-frequency electrical stimulation [16], and neurofeedback therapy [17], 16 studies focused on UCP, two studies adopted interventions pooled as Yoga [15,18], two studies used massage [19,27], two studies used interventions pooled as Edu, including cognitive behavioral therapy [20] and electronic symptom management system [22], six studies used Acu [23-26, 29, 30], one used vitamin and gabapentin (VG [24]), one used photobiomodulation (PBM [21]), and one used ME [28]. There were statistical differences between massage and Acu, VG, and UCP.…”
Section: Primary Outcomes Painmentioning
confidence: 99%
“…Fourteen studies applied other scales for assessment [14,21,27,34,[42][43][44][45][46][47][48][49][50][51], involving 857 participants. One four-arm trial [43] conducted direct a comparison among Acu, hydroelectric baths (HEB), vitamin, and UCP, one study used ES, one three-arm study conducted a direct comparison among SMT, RT, and UCP [44], five studies used massage [27,42,45,46,51], four study used ME [34,47,48,50], and one study used PBM [21]. A close loop of the network map was formed by SMT, RT, and UCP.…”
Section: Peripheral Neuropathological Symptoms-other Scalesmentioning
confidence: 99%